Ethnic Minorities and Their Health Needs: Crisis of Perception and Behaviours. (April 2014) - Wankhade, Paresh; Cook, Ian G.; Halsall, Jamie P.
There is considerable evidence to suggest that racial and ethnic disparities exist in the provision of emergency and wider healthcare. The importance of collecting patient ethnic data has received attention in literature across the world and eliminating ethnic and racial health equalities is one of the primary aims of healthcare providers internationally. The poor health status of certain racial and ethnic groups has been well documented. The improvement of racial and ethnic disparities in healthcare is at the forefront of many public health agendas. This article addresses important policy, practice, and cultural issues confronted by the pre-hospital emergency care setup. This aspect of care plays a unique role in the healthcare safety net in providing a service to a very diverse population, including members of ethnic and racial minorities. Competent decision making by the emergency care practitioners requires patient-specific information and the health provider's prior medical knowledge and clinical training. The article reviews the current ethnicity trends in the UK along with international evidence linking ethnicity and health inequalities. The study argues that serious difficulties will arise between the health provider and the patient if they come from different backgrounds and therefore experience difficulties in cross-cultural communication. This adversely impacts on the quality of diagnostic and clinical decision making for minority patients. The article offers few strategies to address health inequalities in emergency care and concludes by arguing that much more needs to be done to ensure that we are hearing the voices of more diverse groups, groups who are often excluded from engagement through barriers such as language or mobility difficulties.